Pengaruh Daya Tarik Wisata Dan Kualitas Pelayanan Terhadap Kepuasan Wisatawan (Survei pada Objek Wisata Green Paradise Kota Pagar Alam) - Yulia Pebrianti; Alditia Detmuliati; Rezza Stevanie Zein R. (TEHBMJ (Tourism Economics Hospitality and Business Management Journal), 2022)
This research is aimed to test the effect of tourism attraction and service quality on tourist satisfaction (survey on Green Paradise Pagar Alam). This research used descriptive quantitative methods that is using questionnaire to the tourist to collect the data. Multiple linear regression analysis is used to compute the parameters by using IBM SPSS ver. 25. The result shows that tourism attraction has no significant effect on tourist satisfaction, service quality has significant effect tourist satisfaction. Tourism attraction need to develop to increase tourist satisfaction to visit Green Paradise Pagar Alam.